2014
DOI: 10.1001/jamasurg.2014.1233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Novel Financial Incentive Program on Operating Room Efficiency

Abstract: A novel FIP improved OR efficiency. Given the small amount of money involved, it seems unlikely that financial incentives were solely responsible. Effectively communicating the importance of TATs and on-time FCSs and publishing individual results more likely increased staff awareness. Teamwork created by linking assignment of points to a team result likely contributed to success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…For example, there is evidence that financial incentive programmes, interviews with stakeholders and the assignment of an appropriate anaesthesiologist can influence turnaround times. 5,15,16 Moreover, psychological factors such as emotional intelligence may affect patient safety as well as perioperative performance. 17,18 This study is subject to certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that financial incentive programmes, interviews with stakeholders and the assignment of an appropriate anaesthesiologist can influence turnaround times. 5,15,16 Moreover, psychological factors such as emotional intelligence may affect patient safety as well as perioperative performance. 17,18 This study is subject to certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature indicates that daily team huddles at the start of shifts result in fewer interruptions during the day and can provide immediate clarification of issues 12 . The use of preoperative huddles has been shown to increase the number of surgeries starting on time 22 and to create a better flow for patients, families, and the surgical team 23 . A study by Toussaint and Berry showed that huddles are able to increase patient satisfaction scores 23 .…”
Section: Basic Huddle Conceptsmentioning
confidence: 99%
“…[4,12,13,[26][27][28][29][30] Factors influencing productivity and timeliness using the turnover time measure have been reported in numerous OR efficiency studies. [12,21,26,[31][32][33][34][35][36] As was noted in the Canadian Paediatric Surgical Wait Times Project, a lack of a standard methodology for measuring the outcomes in these studies limits the ability to benchmark externally. [4] While there is a plethora of literature focusing on OR efficiency, to our knowledge this is the first study using a matrix of four metrics to measure, benchmark and report monitor OR efficiency that can benchmark improvements over time.…”
Section: Discussionmentioning
confidence: 99%